2017
DOI: 10.17221/64/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilization, burning, and grazing on plant community in the long-term fenced grasslands

Abstract: Fencing is the common management practice to restore degraded grasslands. However, long-term fencing decreases grassland productivity and species diversity. The study was therefore conducted as a three-year (2011–2013) experiment with a randomized complete block in a grassland fenced for 20 years in the Loess Plateau of China, and the effects of fertilization, burning and grazing on aboveground biomass, species and functional group composition, species and some functional group diversity were analysed. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…In this study, the alpha diversity of communities with different years of fencing revealed a significant difference. It can be seen from Table 1 that compared with a lightly grazed meadow, the diversity and evenness of the fenced meadow steppes are significantly reduced, consistent with research results [5,6,[37][38][39][40]. Among these, the evenness tends to gradually decrease with the increase of the years of fencing.…”
Section: Plant Investigationsupporting
confidence: 85%
“…In this study, the alpha diversity of communities with different years of fencing revealed a significant difference. It can be seen from Table 1 that compared with a lightly grazed meadow, the diversity and evenness of the fenced meadow steppes are significantly reduced, consistent with research results [5,6,[37][38][39][40]. Among these, the evenness tends to gradually decrease with the increase of the years of fencing.…”
Section: Plant Investigationsupporting
confidence: 85%